Role of microRNAs in the Regulation of α-Synuclein Expression: A Systematic Review - Recasens, Ariadna; Perier, Celine; Sue, Carolyn M. (Frontiers in Molecular Neuroscience, 2016)
Growing evidence suggests that increased levels of α-synuclein might contribute to the pathogenesis of Parkinson’s disease (PD) and therefore, it is crucial to understand the mechanisms underlying α-synuclein expression. Recently, microRNAs (miRNAs) have emerged as key regulators of gene expression involved in several diseases such as PD and other neurodegenerative disorders. A systematic literature search was performed here to identify microRNAs that directly or indirectly impact in α-synuclein expression/accumulation and describe its mechanism of action. A total of 27 studies were incorporated in the review showing evidences that 6 microRNAs directly bind and regulate α-synuclein expression while several miRNAs impact on α-synuclein expression indirectly by targeting other genes. In turn, α-synuclein overexpression also impacts miRNAs expression, indicating the complex network between miRNAs and α-synuclein. From the current knowledge on the central role of α-synuclein in PD pathogenesis/progression, miRNAs are likely to play a crucial role at different stages of PD and might potentially be considered as new PD therapeutic approaches.